Antidepressant-like effects of dezocine in mice: involvement of 5-HT1A and κ opioid receptors. Issue 6 (September 2021) - Shang, Li; Duan, Cunhao; Chang, Shui; Chang, Ning; Jia, Shushan
Abstract : Dezocine is an opioid with low efficacy at μ-opioid and κ-opioid receptors. It also inhibits the reuptake of norepinephrine and serotonin. Dezocine is an effective analgesic against various clinical painful conditions and is widely used in many Asian countries. Given the unique pharmacology of dezocine, the drug may also have antidepressant-like properties. However, no published preclinical study has explored this possibility. This study examined the potential antidepressant-like activity of dezocine in mice. Male ICR mice were used in the forced swimming test, the tail suspension test, the warm water tail withdrawal test and locomotor activity test to test the effects of dezocine (0.3–3.0 mg/kg). The 5-HT1A receptor antagonist WAY-100635 (1 mg/kg), the μ-opioid receptor antagonist β-funaltrexamine (2 mg/kg) and the κ-opioid receptor agonist U50488 (1 mg/kg) were also studied in combination with dezocine. Dezocine produced a dose-dependent decrease in the immobility time in the forced swimming test and tail suspension test at doses that did not alter the motoric activity as determined in the locomotion test. WAY-100635 and U50488 but not β-funaltrexamine pretreatment significantly blocked the effects of dezocine. Dezocine dose-dependently increased the latency in the tail withdrawal test which was blocked by WAY-100635 and β-funaltrexamine. Combined, these results suggest that dezocine may have antidepressant-like effects. Considering the well-documented analgesic property of dezocine, it may be useful to treat pain and depression comorbidity.